2006 IEEE Nuclear Science Symposium Conference Record 2006
DOI: 10.1109/nssmic.2006.354367
|View full text |Cite
|
Sign up to set email alerts
|

Proton Radiography Studies for Proton CT

Abstract: We report the results of a beam experiment to develop proton Computed Tomography (pCT). The setup consists of telescopes of silicon strip detectors at the entrance and exit of a phantom to predict the path of the proton within the phantom and of a crystal calorimeter to measure the proton energy loss with high precision. The energy loss permits calculating the integrated proton stopping power along each proton path from which the electron density distribution can be reconstructed. We describe the 2D-image reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…For example, Fabrikant et al (1982) reported scanning a metastatic melanoma in the cerebral cortex of a patient with a 670 MeV/n neon ion beam. Schulte et al (2004) and Petterson et al (2006) measured the tracks of individual protons using both entrance and exit Si detectors and energy loss using scintillator-based calorimeters. Later, Schulte et al (2005) and gave specifications for a proton CT scanner both for imaging for treatment planning (optimized for accuracy) and for treatment verification (optimized for speed).…”
Section: Ion Computed Tomography Scanningmentioning
confidence: 99%
“…For example, Fabrikant et al (1982) reported scanning a metastatic melanoma in the cerebral cortex of a patient with a 670 MeV/n neon ion beam. Schulte et al (2004) and Petterson et al (2006) measured the tracks of individual protons using both entrance and exit Si detectors and energy loss using scintillator-based calorimeters. Later, Schulte et al (2005) and gave specifications for a proton CT scanner both for imaging for treatment planning (optimized for accuracy) and for treatment verification (optimized for speed).…”
Section: Ion Computed Tomography Scanningmentioning
confidence: 99%
“…estimated in [11]: in a volume of 10 × 10 × 10 cm 3 , about 10 9 tracks have to be measured. Present state-of-the-art pCT prototypes made excellent advancements in the field, but they still show some limitations for a practical implementation.…”
Section: Proton Computed Tomographymentioning
confidence: 99%
“…The number of required protons has been estimated in Refs. [7] and [8], where the image quality was compared to the number of proton histories in the voxels. Stable solutions were found with 25 proton histories.…”
Section: Design Of the Pct Head Scannermentioning
confidence: 99%